Pengaruh pendapatan asli daerah dan dana perimbangan terhadap belanja langsung dan belanja tidak langsung serta pertumbuhan ekonomi di indonesia - Lisa, Yulianus; Priyagus, Priyagus; Roy, Juliansyah (FORUM EKONOMI, 2017)
The aim of this research is to analyze the influence of Local Revenue and Fiscal Balance Transfers on the Direct and Indirect Expenditures as well as on the Economic Development in Indonesia. The variables in this research were Local Revenue and Fiscal Balance Transfers as independent variables whereas Direct, Indirect Expenditures and Economic Developments were the dependent variables. The sample included 33 provinces in Indonesia over the period of 2009 to 2013. The research findings indicated that the Local Revenue and Fiscal Balance Transfers had a positive and significant influence on the Direct and Indirect Expenditures. In addition, Local Revenue and Fiscal Balance Transfers had a negative influence on the economic development through Direct Expenditure and had a positive, significant influence on the economic development through the Indirect Expenditure.Keywords : Local Revenue,Fiscal Balance Transfers on the Direct, Indirect Expenditures and on the Economic Development in Indonesia